(untitled) (Seminário Internacional de Informação, Tecnologia e Inovação, 2025)
This article investigates the relevance of the social network TikTok in promoting reading, focusing on digital cultural agents located in the state of Alagoas. Adopting a qualitative and quantitative approach, the research combines a literature review and netnography with an analysis of active profiles within the BookTok community. Content published between August and December 2023 was analyzed, considering engagement metrics such as likes, comments, and posting frequency. The results indicate that, although the number of literary creators from Alagoas is small, user engagement is not directly related to the number of followers. Factors such as publishing consistency, community ties, and audience identification with the content proved to be more relevant. The conclusion is that TikTok has potential as a tool for encouraging reading, especially among young people, by integrating literary cultural practices into the dynamics of social media.